First detection of Crenosoma vulpis in Red Foxes Vulpes vulpes in Western Poland - Matysiak A.; Kwiatkowska P. K.; Kaźmierczak S.; Ondrejkova A.; Wasielewski O.; Tryjanowski P. (Helminthologia)
Crenosoma vulpis is a nematode from the superfamily Metastrongylidea, which parasitizes the respiratory tracts of carnivores, primarily red foxes (Vulpes vulpes), and occasionally domestic dogs (Canis familiaris). This study aimed to assess the presence of C. vulpis in red foxes in western Poland, an area where its occurrence had not been previously documented. We examined lung tissue from 47 red foxes obtained during the regular hunting season (2017 – 2018) using the Baermann method to detect the presence of nematode larvae. Larvae, identified based on morphology as C. vulpis, were found in 12.8 % of the foxes (6/47; 95 % CL = 4.8 – 25.7 %). This is the first confirmed report of Crenosoma vulpis in red foxes in Poland, highlighting the potential need for further epidemiological studies on its distribution and impact on both wildlife and domestic animals.